Red blood cell and platelet transfusion support in the first 30 days after autologous stem cell transplantation: real-world data - Sari, Oznur; Ure, Umit Barbaros (Journal of the Pakistan Medical Association, 2026)
Objective: To assess data on transfusion requirements and burdens after autologous stem cell transplantation for haematological malignancy, and to investigate the impact of transfusion requirements and burdens on patient survival outcomes. Method: The retrospective, single-centre study was conducted at Koç University Hospital, Istanbul, Turkiye, and comprised transfusion data of adult patients who underwent autologous stem cell transplantation for haematological malignancies between October 2016 and July 2023. The relationship of transfusion data with transplant and demographic characteristics of the patients was examined along with their impact on patient survival outcomes. Data was analysed using SPSS 21. Results: Of the 331 patients, 176(53%) were male and 155(47%) were female. The median age of the cohort was 56 years (interquartile range: 46-64 years). Overall, 198(59.8%) patients required red blood cell transfusion support, and management of 328(99.1%) necessitated platelet transfusion support. Advanced age, female gender, low pre-transplant haemoglobin levels and a diagnosis of non-Hodgkin’s lymphoma were significantly associated with increased red blood cell transfusion requirements (p<0.05). A diagnosis of non-Hodgkin’s lymphoma and low pre-transplant platelet levels were significantly associated with platelet transfusion burden (p<0.05). A significant difference in overall survival was observed between red blood cell transfused and non-transfused patients (p=0.031). A high transfusion burden of platelets did not significantly impact overall survival (p=0.109). Conclusion: In patients having undergone autologous stem cell transplantation, increased red blood cell transfusion requirement was associated with survival outcome. Key Words: Autologous stem cell transplantation, Red blood cell transfusion, Platelet transfusion.